2015
DOI: 10.4244/eijy14m05_03
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study of a bioabsorbable polymer-coated sirolimus-eluting stent: results of the DESSOLVE II trial

Abstract: The DESSOLVE II trial demonstrated superiority in the primary efficacy endpoint of nine-month mean LLL for APSES compared to ZES. Strut coverage by OCT was high with both stents and the clinical safety endpoints including stent thrombosis were equally low in both groups. ClinicalTrials.gov Identifier: NCT01294748.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…It was concluded that, in real world, the rates of early and midterm scaffold thrombosis, mostly clustered within 30 days, were not negligible. Another trial (64), that compared the MiStent bioabsorbable polymer sirolimuseluting stent with zotarolimus-drug eluting stent, showed superiority in the primary efficacy endpoint of 9-month mean late lumen loss for absorbable polymer sirolimuseluting stent compared to zotarolimus-eluting stent. However, in this trial, the 9-month stent thrombosis rate as defined by the Academic Research Consortium was 0.9% in 117 patients with absorbable polymer sirolimus-eluting stent and 1.7% in 60 patients with zotarolimus-eluting stent.…”
Section: Bioresorbable and Bioabsorbable Stent Advantages Disadvantamentioning
confidence: 99%
“…It was concluded that, in real world, the rates of early and midterm scaffold thrombosis, mostly clustered within 30 days, were not negligible. Another trial (64), that compared the MiStent bioabsorbable polymer sirolimuseluting stent with zotarolimus-drug eluting stent, showed superiority in the primary efficacy endpoint of 9-month mean late lumen loss for absorbable polymer sirolimuseluting stent compared to zotarolimus-eluting stent. However, in this trial, the 9-month stent thrombosis rate as defined by the Academic Research Consortium was 0.9% in 117 patients with absorbable polymer sirolimus-eluting stent and 1.7% in 60 patients with zotarolimus-eluting stent.…”
Section: Bioresorbable and Bioabsorbable Stent Advantages Disadvantamentioning
confidence: 99%
“…Table 1 summarizes the results of the main randomized clinical trials on these novel SES that are either polymer free or use a biodegradable polymer [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. As discussed, microporous metal platforms currently allow one to retain on the stent surface the desired concentrations of the drug whereas other platforms provide sophisticated designs with microreservoirs to hold the pharmaceutical product [3].…”
Section: Trials With Novel Sirolimus-eluting Stentsmentioning
confidence: 99%
“…The theoretical attractiveness of polymer-free and fully bioresorbable polymer DES over permanent polymer DES is clear. Nevertheless, additional studies and, in particular, a very long-term follow-up of existing trials [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] are required to convincingly demonstrate the clinical benefit of these innovative devices.…”
Section: Trials With Novel Sirolimus-eluting Stentsmentioning
confidence: 99%
“…The subsequent, larger DESSOLVE II trial (NCT01294748) compared the efficacy and safety of the MiStent with a first generation Zotarolimus-eluting stent, Endeavor™ (E-ZES; Medtronic, Santa Rosa, USA) [75]. A total of 184 patients were randomized in a 2:1 fashion with MiStent (n=123) versus E-ZES (n=61).…”
Section: Clinical Trials Of Bioabsorbable Polymer-coated Desmentioning
confidence: 99%